Hakikat Pendidik Dan Peserta Didik Dalam Filsafat Pendidikan Islam - Sulis Tyaningsih; Yurna Yurna (Jurnal Budi Pekerti Agama Islam, 2024)
The background about the truth of educators and learners in the philosophy of Islamic education is based on the fundamental principles of Islam and its philosophical views. The Islamic philosophy of education emphasizes the importance of education as a means of achieving the ultimate goal of mankind, which is to approach God, to attain wisdom, and to build a just and moral society. The extent of the Quran in the concept of education has prompted the author to dig one of these concepts, for that in this study the author will try to expose a little about one of the concepts such, that is, that relates to the subject of education in the hope of being able to better understand how subjects of education according to the Quran. The study discussed in this article is a library study that attempts to present in a descriptive way with qualitative and library research methods i.e. library-based research, in the process of data collection, researchers conduct research and analyze library sources obtained from theories from literary books. (library research). One of the important elements in the educational process is the educator. In general, educators are those who have the responsibility to educate. While in particular, the educators in the perspective of Islamic education are the people who are responsible for the development of pupils by seeking to develop all potential pupils, both affective, cognitive, and psychomotor potential in accordance with the values of the teachings of Islam. While pupils are subjects and objects of education that require guidance of others (educators) to help direct and develop the potential that they have. The relationship between the teacher and the student gives each other inseparable roles, the task of the educator is to help the student to be able to adapt to himself and the various challenges of his life, while the role of the pedagogue is as a leader and educator in a society and at the same time as a member of the community, so that the teacher or educators are required in improving their duties and roles. In order to advance education and Islamic needs to be a balance between Islamic and general insight. For that, educators and pupils really must perform their duties and duties well.